2020
DOI: 10.18502/jost.v6i2.4784
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Coronavirus Disease-2019 among Healthcare Workers in Imam Khomeini Hospital Complex in Tehran, Iran

Abstract: Background: The novel coronavirus disease-2019 (COVID-19) has become a significant worldwide problem since January 2019. Hospitals have spent most of their time and logistics on patients with COVID-19. During this crisis, many healthcare providers have been infected with the disease, and occasionally, some wards and operating rooms were shut down as a result. Here, we explain our experience with the healthcare staff involvement with COVID-19 in our hospital. Methods: As a referral tertiary center, Imam K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Several studies have assessed the seroprevalence of SARS-CoV-2 antibodies in HCWs of medical centers in Iran. These reports revealed that seroprevalence varies widely, with rates as high as 23% and as low as 5% [13,14,19], and this range may reflect the difference in COVID-19 burden in different cities of Iran. In comparison with other countries, the prevalence of COVID-19 among the HCWs in Dutch hospitals [20], British teaching hospitals [21], and Denmark [15] revealed that the seroprevalence rates of SARS-CoV-2 are 6%, 3%, and 4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have assessed the seroprevalence of SARS-CoV-2 antibodies in HCWs of medical centers in Iran. These reports revealed that seroprevalence varies widely, with rates as high as 23% and as low as 5% [13,14,19], and this range may reflect the difference in COVID-19 burden in different cities of Iran. In comparison with other countries, the prevalence of COVID-19 among the HCWs in Dutch hospitals [20], British teaching hospitals [21], and Denmark [15] revealed that the seroprevalence rates of SARS-CoV-2 are 6%, 3%, and 4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…he severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the cause of coronavirus disease 2019 (COVID- 19), was first identified in Wuhan, China, in December 2019. COVID-19 spread rapidly worldwide, and World Health Organization (WHO) declared COVID-19 a pandemic on March 11, 2020 [1].…”
Section: Introductionmentioning
confidence: 99%
“…The novel coronavirus pneumonia disease 2019 (COVID-19) outbreak spread out the entire world and became a terrible tragedy. Since the Health Care Professionals (HCPs) carry almost all the burden as the first line and have tolerated a lot of morbidities and mortalities, it is a top priority to prevent intrahospital transmission (1). Ample documents have shown that the COVID-19 virus is transmitted via droplets, small 5-10 μm particles, in direct person-toperson contacts (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…passing were reported. Early in the outbreak, 2 COVID-19related deaths were reported in Qom (8,10). Because of the high case numbers and expanded numbers of COVID-19 patients in healing centers, prohibiting all mass gatherings (restaurant closures, etc.)…”
Section: Introductionmentioning
confidence: 99%